Application in the optimization of Pb(II) adsorption by chitosan from produced water by using response surface methodology - Gul Zaman, H. (Springer Science and Business Media Deutschland GmbH, 2022)
Produced water (PW) generated by the oil and gas industries is deemed the largest waste stream and contains a high toxic pollutant concentration. Hence, it is essential to eliminate or reduce its concentration to an acceptable level before discharge. The present study aims to optimize the reaction conditions in response surface methodology (RSM) via central composite design (CCD) for lead removal from synthetic PW using commercially available chitosan as an adsorbent. A statistically significant model was developed for lead removal through regression analysis (R2 = 0.99). The highest predicted Pb(II) removal value at optimal conditions was 89.12. The Pb(II) adsorption optimal values were at the following conditions; an adsorbent dose of 1.9Â g/L, 4.5 pH, 4Â mg/L of concentration, and 76Â min of contact time. The results of adsorption isotherms and kinetics showed that data fitted well to Langmuirâs and kinetics Pseudo-second-order model (R2 = 0.99). The CCD based on RSM employed for the optimization via adsorption ensured maximum Pb(II) removal. This study could suggest a successful use of eco-friendly and cost-effective adsorbents for real PW treatment. Graphical abstract: Figure not available: see fulltext. Â© 2022, Islamic Azad University (IAU).